Automation of conceptual design and modification of aircraft-type unmanned aerial vehicles using multidisciplinary optimization and evolutionary algorithms. Part 2: results and analysis - V. A. Komarov; O. E. Lukyanov; V. H. Hoang; E. I. Kurkin; J. G. Quijada Pioquinto (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
An example of practical application of the methodology of multidisciplinary optimization of the concept parameters of aircraft-type flight vehicles is considered in the form of solving the problem of modifying two existing aircraft with characteristics presented in open sources. The convergence of the optimization problem was investigated. The results of validation of mathematical models of aerodynamics are presented by comparison with the experiment results. An assessment of the reliability of the calculation of the objective function was carried out using the example of solving the direct problem of calculating the take-off weight and flight performance characteristics of prototype aircraft and comparing the results with their real characteristics. A method for longitudinal trim of aircraft-type flight vehicles with two lifting surfaces with parameter optimization is proposed.